663 A Multi-centre National Study of the Effectiveness of Virtual Fracture Clinic Management of Orthopaedic Trauma during the COVID-19 Pandemic (MAVCOV): A Cross-sectional Study Protocol. (12th October 2021) - Ng, Z H; Downie, S; Makaram, N; Kolhe, S; Mackenzie, S; Clement, N; Duckworth, A; White, T
Abstract: Aim: Virtual fracture clinics (VFCs) are advocated by recent British Orthopaedic Association Standards for Trauma and Orthopaedics (BOASTs) to efficiently manage injuries during the COVID-19 pandemic. The primary aim of this national study is to assess the impact of these standards on patient satisfaction and clinical outcome amid the pandemic. The secondary aims are to determine the impact of the pandemic on demographics of injuries presenting to the VFC and to compare outcomes and satisfaction when the BOAST guidelines were first introduced with a subsequent period when local practice would be familiar with these guidelines. Method: This is a national cross-sectional cohort study comprising centres with VFC services across the United Kingdom. All consecutive adult patients assessed at VFC pre-lockdown (6 May 2019 to 19 May 2019) and at the peak of the first lockdown (4 May 2020 to 17 May 2020), and a randomly selected sample during the second wave (October 2020) will be eligible for the study. Data comprising local VFC practice, patient and injury characteristics, unplanned re-attendances, and complications will be collected. A telephone questionnaire will be used to determine patient satisfaction and patient-reported outcomes for patients who were discharged following VFC assessment without face-to-face consultation. Results: As of 31 October 2020, 51 hospitals with VFC services have been recruited to participate in this study. Conclusions: The study results will identify changes in case-mix and numbers of patients managed through VFCs, due to urgent necessity, and whether this is safe and is associated with patient satisfaction to inform future clinical practice.